Frequency, risk factors, and clinical outcomes of late-onset atrial flutter in patients after heart transplantation - Rahm, Ann-Kathrin; Reinhardt, Susanne; Helmschrott, Matthias; Darche, Fabrice Fernand; Bruckner, Thomas; Lugenbiel, Patrick; Thomas, Dierk; Ehlermann, Philipp; Sommer, Wiebke; Warnecke, Gregor; Frey, Norbert; Rivinius, Rasmus (Journal of cardiovascular development and disease, 2022)
Aims: Atrial flutter (AFL) is a common late-onset complication after heart transplantation (HTX) and is associated with worse clinical outcomes. Methods: This study investigated the frequency, risk factors, and outcomes of late-onset post-transplant AFL. We analyzed 639 adult patients undergoing HTX at the Heidelberg Heart Center between 1989 and 2019. Patients were stratified by diagnosis and type of late-onset post-transplant AFL (>90 days after HTX). Results: A total of 55 patients (8.6%) were diagnosed with late-onset post-transplant AFL, 30 had typical AFL (54.5%) and 25 had atypical AFL (45.5%). Patients with AFL were younger at HTX (p = 0.028), received more biatrial anastomosis (p = 0.001), and presented with moderate or severe tricuspid regurgitation (56.4%). Typical AFL was associated with graft rejection (p = 0.016), whereas atypical AFL was associated with coronary artery disease (p = 0.028) and stent implantation (p = 0.042). Patients with atypical AFL showed a higher all-cause 1-year mortality (p = 0.010) along with a higher rate of graft failure after diagnosis of AFL (p = 0.023). Recurrence of AFL was high (83.6%). Patients with catheter ablation after AFL recurrence had a higher 1-year freedom from AFL (p = 0.003). Conclusions: Patients with late-onset post-transplant AFL were younger at HTX, received more biatrial anastomosis, and showed a higher rate of moderate or severe tricuspid regurgitation. Typical AFL was associated with graft rejection, whereas atypical AFL was associated with myocardial ischemia, graft failure, and mortality. Catheter ablation represents a viable option to avoid further episodes of late-onset AFL after HTX.
Gesehen am 04.01.2023